Enterprise Content Management Implementation and Risk - Jaroslava Klegová; Ivana Rábová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2015)
Enterprise Content Management (ECM) solutions are commonly used in many areas such as document management, record management, digital asset management, etc. Key features of ECM systems are capturing, indexing, preserving and retrieving of digital information. The state-of-the- art ECM solution can help revolutionize document management and further automated business processes which can lead to better decisions and competitive advantage. Risk management can reduce project failure and that is why controlling risk in ECM implementation projects is considered to be a major contributor to project success. To manage software risk, the first step is to identify a list of ECM projects’ risks. The present paper provides an overview of ECM implementation risks and contains findings from a small survey on experience of ECM implementation and risk in Czech enterprises. Risk of implementation in the public sector is discussed more deeply with case study examples.